2002
DOI: 10.1177/0013164402062001006
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Factors Influencing Pursuit of Higher Education Questionnaire

Abstract: This article addresses the development and validation of the Factors Influencing Pursuit of Higher Education (FIPHE) Questionnaire, a 92-item self-report measure that investigates factors that influence individuals to pursue higher education. Reliability estimates for the nine FIPHE scale scores ranged from .66 to .90. An exploratory factor analysis was conducted on data from a sample ( N = 509) of college students enrolled in two south-eastern universities. The data were subjected to principal components anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For instance, the economic perspective of Hossler et al's (1999) model concentrates on the cost-benefit aspect of the financial burden and contributions of higher education to high-paying jobs and social status. This perspective overlaps with the relative functionalism factor advocated by Harris and Halpin (2002), or the instrumental values of education, compared to other non-educational choices. Scholarships and financial aid are crucial in enabling low-income students to attend college and cultivate their talent.…”
Section: The Conceptual Modelsmentioning
confidence: 91%
See 2 more Smart Citations
“…For instance, the economic perspective of Hossler et al's (1999) model concentrates on the cost-benefit aspect of the financial burden and contributions of higher education to high-paying jobs and social status. This perspective overlaps with the relative functionalism factor advocated by Harris and Halpin (2002), or the instrumental values of education, compared to other non-educational choices. Scholarships and financial aid are crucial in enabling low-income students to attend college and cultivate their talent.…”
Section: The Conceptual Modelsmentioning
confidence: 91%
“…The primary objective of this study is to scrutinize the crucial variables that influence students' inclination and endeavor toward attaining higher education, particularly across diverse student groups. In order to accomplish these research aims, we have identified the factors espoused by the Combined model (Hossler et al, 1999) and Harris and Halpin's (2002) model as instrumental in shaping our study. Both models share overlapping and complementary factors.…”
Section: The Conceptual Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of understanding the factors that make individuals adopt certain behaviors, a series of studies and models have been developed that aim to explain them (Harris and Halpin, 2002;Islam and Jahan, 2014;Ng et al, 2011;Nyaribo et al, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The survey was based on the Factors Influencing Pursuit of Higher Education (FIPHE) Questionnaire developed by Harris and Halpin. 6 There are 114 questions ranging from how long they have lived in their current home to the size and diversity of their high school, to opinions expressed by friends and family regarding their pursuit of an undergraduate engineering degree. Due to its length, the actual survey is not included in this paper.…”
Section: Profile Of Hypatiansmentioning
confidence: 99%